Sex differences in kappa opioid receptor antinociception is influenced by the number of X chromosomes in mouse. Issue 1 (30th July 2020) - Taylor, Anna M. W.; Chadwick, Caylin I.; Mehrabani, Sadaf; Hrncir, Haley; Arnold, Arthur P.; Evans, Christopher J.
Abstract: Kappa opioid receptor (KOR) agonists produce robust analgesia with minimal abuse liability and are considered promising pharmacological agents to manage chronic pain and itch. The KOR system is also notable for robust differences between the sexes, with females exhibiting lower analgesic response than males. Sexually dimorphic traits can be due to either the influence of gonadal hormones during development or adulthood, or due to the complement of genes expressed on the X or Y chromosome. Previous studies examining sex differences in KOR antinociception have relied on surgical or pharmacological manipulation of the gonads to determine whether sex hormones influence KOR function. While there are conflicting reports whether gonadal hormones influence KOR function, no study has examined these effects in context with sex chromosomes. Here, we use two genetic mouse models, the four core genotypes and XY*, to isolate the chromosomal and hormonal contributions to sex differences in KOR analgesia. Mice were treated with systemic KOR agonist (U50, 488H) and thermal analgesia measured in the tail withdrawal assay. We found that KOR antinociception was influenced predominantly by the number of the X chromosomes. These data suggest that the dose and/or parental imprint on X gene(s) contribute significantly to the sexually dimorphism in KOR analgesia. Abstract : The kappa opioid receptor (KOR) is notable for its robust sex difference, with females being less responsive to KOR agonists than males. In this study, we use two genetic mouse models (four core genotype and XY*) to isolate the sex chromosome and gonadal hormone contribution to this observed sex difference. We determine that KOR analgesia varies with the number of X chromosomes. The presence or absence of the Y chromosome or gonadal hormones had minimal influence. This study determines that genes on the X chromosome contribute to the sex difference in KOR function.